Influence Of Moisture Content On Some Physical Properties Of Baobab Seeds (Adansonia Digitata) In Relation To Equipment Development For Postharvest Processing And Handling. (JOURNAL OF ADVANCES IN AGRICULTURE, 2022)
In this study, the effect of moisture content on the physical attributes of baobab seeds was examined, along with the implications for the design of machinery for postharvest handling and processing of the seeds. The seed's volume, sphericity, aspect ratio, axial dimensions, arithmetic, and geometric mean diameters were all determined. Gravimetric properties including porosity, bulk density, and thousand grain mass were measured. Additionally, the seeds' frictional characteristics on different surfaces for handling after harvest were established. The arithmetic and geometric mean diameters were found to be in a range of 8.00 and 9.64 mm and 7.86 and 9.50 mm, respectively, with moisture contents between 5.4 and 20.6% on a dry basis. The seed's sphericity ranged from 78.18 to 80.38 percent. Densities for the bulk and particle ranged from 740.77 to 763.40 kg/m3 and 1155.22 to 1223 -29 kg/m3, respectively. The study revealed that among the four frictional surfaces, plywood surface had the greatest resistance to the flow of the seeds, and the least was registered for the glass surface material. The effect of moisture content on the seed’s physical properties were statistically significant (p≤0.05). Regression equations for future predicting the various physical properties at different moisture contents were developed. The study has produced valuable information that will help with the design of machinery for handling and processing baobab seeds after harvest.